(untitled) (International Conference on Multidisciplinary Sciences and Educational Practices, 2025)
Metaphorical expressions, which are considered to be the most widely used type of stylistic devices in linguistics makes language imagery and it plays an important role in literature. In this article, metaphor in literature and its essence are clarified. Firstly, the semantic aspect of metaphorical expressions is uncovered then there is information about its stylistic features with different examples. By highlighting the role of metaphorical expressions in literature, this article aims to clarify its influences on literary texts.